2009
DOI: 10.1179/174328408x382181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron on removal of iron from aluminium melts

Abstract: Effect of boron on iron removal and the feasibility of formation of iron borides in Al melt were studied. The iron composition was not reduced by the addition of boron. Analysis using SEM/EDX and XRD indicated the formation of titanium and vanadium borides in the melt and no iron borides were detected. Thermodynamic calculations proved that iron cannot react with the added boron in the melt to form iron borides under the experimental conditions, and the lowest Fe concentration that can be purified by boron add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…As reported by Wang (2005), the morphology of AlB 2 was platelet or bulk. No iron borides were found, which was consistent with our previous study (Gao et al, 2009b).…”
Section: Resultssupporting
confidence: 93%
“…As reported by Wang (2005), the morphology of AlB 2 was platelet or bulk. No iron borides were found, which was consistent with our previous study (Gao et al, 2009b).…”
Section: Resultssupporting
confidence: 93%
“…This is not consistent with the literature, but can be attributed to the percentage of Fe content, which is lower in this sample ( Table 1). As described in the literature 14,15 the primary influence on the electrical properties can be connected to the chemical composition. This is also supported by Equation (1), which describes the electrical resistivity r for resistors that have a uniform cross-section A with a uniform flow of electric current on length l, and are made of one material with the electrical resistance value R:…”
Section: Resultsmentioning
confidence: 99%
“…These reactions reduce the number of free electrons, which are determining the electrical conductivity values. [13][14][15] Most available researches of electrical resistivity are based on aluminium alloys with silicon, [16][17][18] which are widely applied in the industry for high-pressure die casting. While the alloys from the group 1xxx are very rarely involved in the research of die casting processes.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of non-reactive impurities in aluminum such as Fe and Ni are of a great challenge to researchers. [22,23,32,33] The removal of high concentration of Fe from molten aluminum using borates was investigated by Gao et al [14] It was reported that the minimum level of Fe that could be achieved using borate additives in molten aluminum is 11.9 wt pct. This level of Fe concentration is much higher than the particular situation under investigation (ppm level).…”
Section: The Kinetics Of Ti Zr Cr and Fe Removal From Aluminummentioning
confidence: 99%
“…Industrially, impurities such as V, Ti, Zr, and Cr are removed in casthouse by the addition of boron bearing substances to the molten aluminum, known as boron treatment. [6][7][8][9][10][11][12][13][14][15][16] In the boron treatment of molten aluminum, Al-B master alloys are added in the form of waffles, ingots, or rods, depending on the process requirement and the required quality of the end product. Al-B master alloys containing AlB 2 or AlB 12 phases are commonly used in the industry.…”
Section: Introductionmentioning
confidence: 99%